Dehiscencia del canal semicircular superior, un nuevo diagnóstico en pacientes con vértigo - Alzérreca A., Eugenio; Pardo J., Javiera; Salas Z., Álvaro; Walker J., Katherine; Délano R., Paul H. (Revista Hospital Clínico Universidad de Chile, 2011)
Introduction: The superior semicircular canal dehiscence syndrome (SSCD) is a pathology described in 1998, which presents several symptoms including sound induced vertigo, hearing loss and autophony due to bone dehiscence of this semicircular canal. Material and Methods: A retrospective and descriptive study was carried out, reviewing the medical records of patients with computed tomography suggestive of SSCD between 2006 and 2010 from the Radiology department of the Clinical Hospital of the University of Chile. Results: We obtained six cases of SSCD (4 female) with a mean age of 52.7 years. SSCD was observed in four cases bilaterallyand in two cases on the left ear. We confirmed a clinical syndrome in two patients, based on the presence of hearing loss and sound induced vertigo. Conclusions: The diagnosis of SSCD syndrome should be supported on both clinical and imaging studies. We should maintain a high level of suspicion, particularly in cases of sound induced vertigo and of conductive hearing loss with normal otoscopy.